Veterans in Counseling Programs: Military Service and the Counselor Training Process - Crystal D Hahn; Carl R Price; Claudia G Interiano-Shiverdecker (Teaching and Supervision in Counseling, 2022)
The authors conducted a transcendental phenomenological study to acquire a deeper understanding of graduate student veterans’ experiences in counselor training programs and explore how military background influences counselor development. Results are based on semi-structured interviews with eight graduate student veterans enrolled in counseling programs across the United States. Four themes resulted which impacted counselor training processes (a) military behaviors, values, and identity (b) military counseling cultural contrasts, (c) integrating military service into counselor training, and (d) veteran-friendly suggestions for counseling programs. This study presented a range of experiences graduate student veterans have in counselor training programs, concluding that this student population provides a unique and valuable cultural perspective that warrants independent consideration and representation in counselor training. We further discuss implications for counselor education and future research to better support this student population.
Keywords: military; student veteran; counselor education; phenomenology; veteran critical theory